GRP-175 Smart Infusion Pumps in Chemotherapy Administration. (12th March 2013) - Garrido, M; Faus, V; Lopez-Martin, C; Arenas, J; Tortajada, B
Abstract : Background: Medication errors, mainly those that occur with high-risk drugs, are associated with high morbidity and mortality. About 38% of these errors occur during the administration phase and only 2% are intercepted. Purpose: To evaluate the use of smart infusion pumps in the oncology area and to assess if this technology reduces intravenous drug administration errors in cancer patients. Materials and Methods: We analysed the information in Signature-Edition ® volumetric infusion pumps for the period January–September 2012 in the oncology area. All infusion pumps were configured with GuardRails ® safety software. The drug library was specifically set up by a clinical pharmacist with all the intravenous drugs usually prescribed to cancer patients. We established maximum and minimum limits for each drug. If the nurse in charge of drug administration exceeded the defined limit, an alarm was displayed to alert her. Results: Over nine months 14, 693 infusions were administrated to 4, 628 patients. The safety system was used in 99.1% of infusions. 768 alarms were triggered, in 5.2% of infusions started. Comprehensive analysis of the alarms showed that 289 (37.6%) were caused by a rate lower than the correct rate and 194 (25.2%) by infusions set at a higher than the established upper limit. 483 drugs had to be reprogrammed. 113 alarms were not associated with a real programming error. Conclusions: Implementation of smart infusion systems based on this safety software can prevent 5% of errors in intravenous drug administration and can help us to enhance the safety of high-risk medicines. The alarms reported are not always associated with a real administration error. It is necessary to review the limits set for some drugs to improve system applicability. No conflict of interest.